All‐cause and cause‐specific mortality among people with regular or problematic cocaine use: a systematic review and meta‐analysis. (21st September 2020) - Peacock, Amy; Tran, Lucy Thi; Larney, Sarah; Stockings, Emily; Santo, Thomas; Jones, Hayley; Santomauro, Damian; Degenhardt, Louisa
Abstract: Aims: To estimate pooled all‐cause and cause‐specific mortality risk for people with regular or problematic cocaine use. Methods: Systematic review and meta‐analysis of prospective or retrospective cohort studies or clinical trials ( n  ≥30) of people with regular or problematic cocaine use with data on all‐cause or cause‐specific mortality. Of 2808 papers, 28 were eligible and reported on 21 cohorts, with a total 170 019 individuals. Cohorts identified based on acute care for drug poisoning or other severe health presentation were excluded. Title/abstract screening was conducted by one reviewer; a second reviewer independently checked 10% of excluded studies. Two reviewers conducted full‐text screening. Data were extracted by one reviewer and checked by a second. A customized review‐specific study reporting quality/risk of bias tool was used. Data on crude mortality rates (CMR) and standardized mortality ratios were extracted for both all‐cause and cause‐specific mortality. Standardized mortality ratios were imputed where not provided by the author using extracted data and information from the Global Burden of Disease Study 2017. Data were pooled using a random‐effects model. Results: The pooled all‐cause crude mortality rate was 1.24 per 100 person‐years [95% confidence interval (CI) = 0.86, 1.78; n  = 16 cohorts], but with considerable heterogeneity ( I 2  = 98.8%). The pooled all‐cause standardized mortality ratio (SMR) was 6.13 (95% CI = 4.15, 9.05; n  = 16 cohorts). Suicide (SMR = 6.26, 95% CI = 2.84, 13.80), accidental injury (SMR = 6.36, 95% CI = 4.18, 9.68), homicide (SMR = 9.38, 95% CI 3.45–25.48) and AIDS‐related mortality (SMR = 23.12, 95% CI = 11.30, 47.31) were all elevated compared with age and sex peers in the general population. Conclusions: There are elevated rates of mortality among people with regular or problematic cocaine use for traumatic deaths and deaths attributable to infectious disease.